Sexual Practices During Adolescence - Arruda,Emanoela Priscila Toledo (2020)
Abstract Adolescence is characterized by significant biological and psychological changes. During this time, the increased production of androgens leads to increased sexual behavior, and this may contribute to early initiation of sexual activity. The objectives of the present cross-sectional study of adolescents enrolled in state schools in the city of Ribeirão Preto, state of São Paulo, Brazil, were to determine the average age at the first sexual intercourse (sexarche), the average number of sexual partners, and the frequency of contraceptive and condom use. Information on the age at sexarche, number of sexual partners, use of different contraceptive methods, and use of condoms were obtained using a semistructured questionnaire. Quantitative variables are expressed as means and standard deviations (SDs), and qualitative variables as absolute and relative frequencies. The chi-squared test was used for comparisons of qualitative variables, and the Student t-test for comparisons of continuous variables. All statistical analyses were performed using SAS (version 9.4, North Carolina State University, USA). We evaluated 202 students who answered the questionnaire, 69 males (36.36%) and 133 females (63.64%). The age at sexarche for men ranged from 7 to 18 years old, and for women from 7 to 17 years old. Forty-eight girls (36.01%) and 21 boys (30.43%) were in the first year of high school, 66.94% of adolescents reported sexual intercourse, and 56.25% used a condom during the first sexual intercourse. A total of 36.72% of students said they had safe sex most of the time, and 83.59% said that the first sexual intercourse happened because they “had a crush on” the other person.